THU0523 Do we need steroid injection after ultrasound guided percutaneous lavage of a rotator cuff calcification ? results at 3 months of a double blinded randomised controlled study. (12th June 2018) - Darrieutort-Laffite, C.; Varin, S.; Coiffier, G.; Albert, J.-D.; Cormier, G.; Le Goff, B.
Abstract : Background: Rotator cuff calcific tendinopathy is a common condition causing up to 20% of the painful shoulder. Ultrasound guided percutaneous lavage (UGPL) is indicated after failure of conservative treatments. Steroids injections in the subacromial bursa (SAB) are usually performed after the lavage to prevent the pain induced by the procedure. However, some suggested that this injection could prevent the inflammatory reaction leading to the disappearance of the calcific deposit. Moreover, its efficacy to prevent post-procedure pain has never been demonstrated. Objectives: The goal of this study was to evaluate the effect of a steroid injection in the SAB after UGPL on the pain and the radiographic evolution of the calcification. Methods: This was a multicentric prospective double blinded randomised controlled study. We included patients with shoulder pain for more than 3 months and a type A or B calcification >5 mm on X-Ray. Patients were treated with UGPL using a single needle technic. At the end of the procedure, they received a blind injection of either 2 mL of methylprednisolone acetate or 2 mL of serum saline. The primary outcome was the maximal VAS pain (0–100) the first week following UGPL. Secondary outcomes were the evolution of VAS pain at 7 days, 6 weeks and 3 months and the radiographic changes of the calcification at 3 months. Results: We included 134 patients, mean age 49.8 (±9.7) years, 89 females (67.4%). Calcifications involved the supraspinatus, infraspinatus and subscapularis in 114 (85%), 14 (10%) and 6 patients (5%) respectively. Calcifications were type A and type B in 42, 5% and 57, 5% of the cases respectively and mean size of the calcification was 1, 5 cm (±0, 5). Backflow of calcific material was obtained in 107 patients (81.1%). Maximum pain during the first week following UGPL was 71.5 [CI95%:63.9–79.20] in the serum saline group versus 59.8 [CI95%:52.2–67.41] in the steroid group with a mean difference of 11.7 [CI95%:3.7–19.7]. More patients in the placebo group needed to take NSAID (12.1% versus 6.1%) and paracetamol (16.7% versus 9.1%) during the first week. VAS pain at rest and during activities decreased significantly more in the steroid group compared to the placebo: VAS pain during activity was 72.02 [62.98–81.06], 26.63 [17.60–35.67], 32.30 [23.11–41.49] and 43.27 [34.18–52.37] in the steroid group versus 72.46 [63.41–81.51], 48.22 [39.14–57.31], 51.44 [42.26–60.62] and 51.09 [41.95–60.24] in the placebo group at day 0, 7, 6 weeks and 3 months respectively (figure 1). At 3 months no difference was found in the radiographic evolution: 62.1% of the patients treated with steroid and 64.8% treated with serum saline had more than 50% of resorption of their calcification. Conclusions: Our study shows that steroid injection in the SAB leads to a significant decrease of maximal pain the following week. This treatment also decreases significantly the pain during the 3 first months after UGPL. Importantly, we found no difference between the 2 groups in the radiographic evolution of the calcification at 3 months. Overall, steroids injections in the SAB can be recommended after UGPL. Disclosure of Interest: None declared